Quick reference to critical care - Diepenbrock, Nancy H. (Wolters Kluwer Health, 2020)
For immediate, on-the-unit answers to ICU questions, get the must-have pocket guide: the fully updated "Quick Reference to Critical Care, 6th Edition". Covering a broad range of critical care topics, each chapter is divided by body system and alphabetically organized, addressing disease processes, disorders, medications and titration, tests, lab results, formulas, ICU equipment and treatment strategies and goals. Information provided is based on current, evidence-based procedures and stabilization practices. This classic, concise quick reference offers crucial guidance on numerous processes and procedures. -- From publisher's description.